2021
DOI: 10.3390/ijms22031184
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Biosynthesis and Plastid Development in Plants: The Role of Light

Abstract: Light is an important cue that stimulates both plastid development and biosynthesis of carotenoids in plants. During photomorphogenesis or de-etiolation, photoreceptors are activated and molecular factors for carotenoid and chlorophyll biosynthesis are induced thereof. In fruits, light is absorbed by chloroplasts in the early stages of ripening, which allows a gradual synthesis of carotenoids in the peel and pulp with the onset of chromoplasts’ development. In roots, only a fraction of light reaches this tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 161 publications
3
43
0
Order By: Relevance
“…Carotenoid biosynthesis regulation in plants has been extensively studied. Although there is much information about how this process is regulated by several factors, there is still much to explore especially respect to how light regulates this process in plant organs that normally grow with no direct W, such as roots (Stanley and Yuan, 2019; Quian-Ulloa and Stange, 2021). With the purpose to understand how carotenoids are synthesized in orange carrot taproot, we compared through RNAseq the expression profile of carrot roots that grew in W respect to those that grew underground (Arias et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carotenoid biosynthesis regulation in plants has been extensively studied. Although there is much information about how this process is regulated by several factors, there is still much to explore especially respect to how light regulates this process in plant organs that normally grow with no direct W, such as roots (Stanley and Yuan, 2019; Quian-Ulloa and Stange, 2021). With the purpose to understand how carotenoids are synthesized in orange carrot taproot, we compared through RNAseq the expression profile of carrot roots that grew in W respect to those that grew underground (Arias et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In shade, the expression of PAR1 , PAR2 and the LONG HYPOCOTYL IN FAR RED 1 ( HFR1 ) is induced, factors that encode transcriptional bHLH cofactors that participate in the compensation of excessive hypocotyl elongation during SAS (Roig-Villanova et al, 2007; Bou-Torrent et al, 2008; Hao et al, 2012; Zhou et al, 2014). From these factors, PAR1 interacts with several bHLH proteins that act as positive regulators of SAS such as BEEs, BIMs and PIFs by partially preventing the binding of these transcription factors to LREs of photomorphogenic genes (Roig-Villanova et al, 2006; Cifuentes-Esquivel et al, 2013; Ballaré and Pierik, 2017; Roig-Villanova et al, 2007; Hao et al, 2012; Stange and Flores, 2012; Zhou et al, 2014; Bou-Torrent et al, 2015; Fernández-Milmanda and Ballaré, 2021; Quian-Ulloa and Stange, 2021). Importantly, PAR1 promotes PSY expression under shade (Bou-Torrent et al, 2015) and, of the positive SAS regulators BEEs, BIMs and PIFs, only PIFs participate in repressing PSY expression and carotenoid synthesis in the shade (Toledo-Ortiz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photolabile PHYB and PHYC mainly exist in the lighted tissue. PHYA and PHYB are mainly involved in photomorphogenesis and carotenoid synthesis of plant, they can also interact with basic helix-loop-helix (bHLH) transcription factors in a conformation specific manner to form phyinteracting interacting factors (PIFs, including PIF1-PIF5), which preferentially bind to many elements of light regulatory promoters, and then regulate the metabolism of pigment compounds (Moon et al 2008 ; Quian-Ulloa et al 2021 ). In response to low R: FR signal, the elongation and growth rate of stems and petioles are increased rapidly and significantly in many plants.…”
Section: Introductionmentioning
confidence: 99%
“…PSY is the first and key enzyme in this process. The transcription and regulation of the gene encoding this enzyme is the main driving force of carotenoid synthesis (Quian-Ulloa et al 2021 ; Toledo-Ortiz et al 2010 ; Zhang et al 2020 ), which are shown in Fig. 2 .…”
Section: Introductionmentioning
confidence: 99%